Online-Offline Teaching for Bio-Pharmaceutical Students During the COVID-19 Pandemic: The Case Study of Advanced Mathematics in Application-Oriented Universities of China - Peng, Weicai; Wang, Shuchao (Frontiers in Public Health, 2022)
Background: With the development of the COVID-19 pandemic, the importance of online teaching is becoming more and more prominent, especially for the basic advanced mathematics majoring in bio-pharmaceutical in colleges. However, the only online teaching model loses efficiency when facing the undergraduates in application-oriented universities. Purpose: How to improve the teaching quality of advanced mathematics has always been a concern because the mathematical abilities of students in application-oriented universities are not ideal. In this paper, we develop a blending online-offline teaching model combined the online teaching and the offline outcome-based education (OBE), as an alternative to traditional offline education. Methodology: The comparative analysis experiment is carried to the two classes undergraduates. The control group and the experimental group are respectively the 2020 class students and the 2021 class students majoring in bio-pharmaceutical. The experimental group students receive the combined teaching method, while the control group students receive the traditional offline education. Results: (1) From the comparative analysis we can find that the students under the online-offline teaching model are more differentiated than that under traditional offline education model. (2) The online-offline teaching model equipped with "case study + knowledge point + applications" process has achieved a good teaching effect in the author's university. Conclusion: The proposed teaching model can well stimulate students' interest in advanced mathematics learning, and resonate with students through actual cases, thereby arousing students' autonomous learning drive, and apply what they have learned to professional fields.